Integration of Coding and Artificial Intelligence (AI) Subjects in Primary School Curriculum as an Effort to Improve 21st Century Skills - Farchan, Achmad (Jurnal Penelitian Pendidikan, 2025)
The integration of coding and atificial intelligence (AI) subjects into the primary school curriculum is a strategic innovation to prepare the younger generation to face the challenges of the 21st century in the digital era and society 5.0. Through coding and AI learning, students are not only taught how to use technology, but also trained to think critically, creatively, collaboratively, and communicatively. This literature review aims to examine the urgency, challenges, and opportunities of integrating coding and AI in primary schools an effort to improve 21st century skills. The results of the study indicate that this integration can strengthen digital literacy, computational thinking skills, and encourage personalised learning that is relevant to future needs. However, the success of implementation depends heavily on infrastructure readiness, teacher competence, and adequate policy support. Multi-stakeholder collaboration is key to overcoming obstacles and ensuring equitable access to quality education. With the right strategies, the integration of coding and AI in primary schools can be a long-term investment in building a generation that is outstanding, adaptive, and ready to compete globally.